A slurry for improving the strength of dry ceramic tiles and its preparation method and application

By using a slurry composed of liquid aluminum dihydrogen phosphate and alumina powder, a three-dimensional network structure is formed to enhance the dry blank of the ceramic tile, which solves the problems of high plasticity clay cost and non-renewability in traditional ceramic production, and achieves a significant increase in the strength of the dry blank of the ceramic tile and reduces the production cost.

CN119775027APending Publication Date: 2025-04-08QINGYUAN GANI CERAMICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510007512.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the production of traditional architectural ceramics, the non-renewability and high cost of high plastic clays have led to a decrease in the drying strength of ceramic blanks, resulting in the dilemma of low yield, difficult to improve production efficiency and product quality.

Method used

The slurry composed of liquid aluminum dihydrogen phosphate and alumina powder is used to enhance the dry blank of the ceramic tile by forming a three-dimensional network structure to improve its strength. The slurry does not require high content of plastic clay and is readily available and at low cost.

Benefits of technology

It significantly improves the strength of the dry blank of ceramic tile, meets the requirements of various production processes, especially the wire mesh process, reduces the frequency of body formula adjustment and the use of raw ore mud, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775027A_ABST
    Figure CN119775027A_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of building ceramics, and particularly relates to a slurry for improving the strength of a dry ceramic tile blank, and a preparation method and application thereof. The slurry comprises liquid aluminum dihydrogen phosphate, aluminum oxide powder, and further comprises phenolic resin, wherein the liquid aluminum dihydrogen phosphate serves as an inorganic binder, the aluminum oxide powder serves as an aggregate, and the phenolic resin serves as an organic binder, which can be composited with each other to form a three-dimensional cross-linked network filling structure to strengthen the blank. The raw materials are easily available and the cost is low. Moreover, when used, the slurry can be directly coated on the bottom of the blank, without involving adjustment of the blank composition, and without affecting other process parameters and performance indicators of the blank, and the strength improvement effect is significant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building ceramics, and in particular to a slurry for improving the strength of dry ceramic tiles, and a preparation method and application thereof. Background Art

[0002] In the traditional building ceramic production process, since highly plastic clay is a non-renewable resource, the proportion of clay with more lean materials has gradually increased, which has led to a decrease in the dry strength of the ceramic body, causing the body to be damaged during the molding, transportation, drying, glazing and other processes. There are many serious defects such as cracks, broken corners, and missing edges, which has seriously reduced the yield rate, affecting the improvement of ceramic production efficiency and product quality.

[0003] The production of marble tiles uses the "inkjet printing + screen printing" process to restore the texture and layered effect of natural marble. This requires that there is no cracking in the bricks during the production process and has high requirements for the dry strength of the tiles. At this stage, it is mainly achieved by adding raw ore mud with a relatively high mass ratio into the blank, but the cost is relatively high.

[0004] At present, the main methods for improving the dry strength of ceramic tiles in building ceramics include:

[0005] (1) Increasing the molding pressure of the press, but when the molding pressure reaches a certain level, the effect of improving the strength of the blank becomes less obvious, and it is easy to cause defects (such as sandwiching, etc.). Moreover, as the pressure increases, the cost and energy consumption of the molding equipment also increase.

[0006] (2) Adjust the green body formula and increase the proportion of high plasticity clay: such as bentonite, raw ore mud, etc., but the research cost is high and the test cycle is long. Increasing the content of high plasticity clay will also increase the drying shrinkage, firing shrinkage and firing temperature of the green body. In addition, there is an upper limit to the amount of clay used in some ceramic raw materials, and the effect of improving the green body strength cannot be achieved by simply increasing the amount of plasticity clay in the ceramic raw materials. Moreover, plasticity clays such as raw ore mud are non-renewable resources, and their sources are becoming increasingly scarce.

[0007] (3) Adding an appropriate amount of green body reinforcing agent, usually adding the green body reinforcing agent to the mud and mixing evenly, and then spray drying and granulation. This method can usually increase the strength of the ceramic green body by 15% to 20%, but it will also form a network structure that wraps the free water in the mud, making the fluidity of the mud worse. To solve this problem, the only way is to continue to increase the amount of water in the mud, but this will lead to an increase in the energy consumption of spray granulation. Therefore, it is necessary to add a deflocculant to reduce the viscosity of the mud, but at the same time it will further increase the production cost.

[0008] Therefore, it is urgent to develop a suitable solution to improve the strength of the green body. Summary of the invention

[0009] In view of this, the present invention provides a slurry for improving the strength of a dry ceramic tile blank and a preparation method thereof, which eliminates the need to introduce a high content of plastic clay into the blank, and the obtained dry ceramic tile blank strength can meet the requirements of various production processes, especially the screen process.

[0010] To achieve the above object, the technical solution adopted by the present invention is:

[0011] In the first aspect, the present invention provides a slurry for improving the strength of a dry tile blank, comprising liquid aluminum dihydrogen phosphate and aluminum oxide powder, wherein the liquid aluminum dihydrogen phosphate is used as an inorganic binder and the aluminum oxide powder is used as an aggregate, which can form a three-dimensional network to strengthen the blank.

[0012] Preferably, in the slurry, the concentration of liquid aluminum dihydrogen phosphate is 50%wt, and the molar ratio of aluminum dihydrogen phosphate:alumina is 1:0.5-2. More preferably, the molar ratio of aluminum dihydrogen phosphate:alumina is 1:1.

[0013] Preferably, the particle size of the aluminum oxide is in the range of 200-300 mesh.

[0014] Preferably, the slurry also contains phenolic resin, which can better cooperate with liquid aluminum dihydrogen phosphate and the like to form a three-dimensional cross-linked network filling structure to reinforce the green body.

[0015] More preferably, in terms of mass ratio, liquid aluminum dihydrogen phosphate: phenolic resin = 10: 2-0.5.

[0016] In a second aspect, the present invention also provides a method for preparing the slurry for improving the strength of a dry ceramic tile blank, wherein the slurry for improving the strength of a dry ceramic tile blank is obtained by uniformly mixing and dispersing the components.

[0017] Preferably, the flow rate of the slurry is in the range of 17-66 s, and the specific gravity is in the range of 1.40-1.61 g / ml.

[0018] In the third aspect, the present invention also provides a method for improving the strength of ceramic tile dry blanks, comprising the steps of uniformly applying the above-mentioned slurry for improving the strength of ceramic tile dry blanks to the bottom of the blank to be dried, and then drying it normally. The strength of the dry blank can be significantly improved without affecting other process parameters and performance indicators of the blank.

[0019] Preferably, the coating thickness of the slurry is 0.3-0.5 mm.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The slurry of the present invention forms a three-dimensional cross-linked network filling structure by the composite action of an inorganic binder (liquid aluminum dihydrogen phosphate) and an aggregate (alumina powder) to reinforce the green body. An organic binder (powdered phenolic resin) can be further introduced. The raw materials are easily available and the cost is low. When used, it can be directly coated on the bottom of the green body without involving the adjustment of the green body components and without affecting other process parameters and performance indicators of the green body. It not only reduces the frequency of adjusting the green body formula, but also reduces the use of high-quality clay such as raw ore mud. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The comparison of the effects of different slurries on enhancing the strength of green bodies in the embodiments of the present invention;

[0023] Figure 2 The effect of liquid A, liquid B and liquid C acting on the bottom of the production line bricks according to the embodiment of the present invention is changed;

[0024] Figure 3 This is a schematic diagram of the slurry enhancement effect of an embodiment of the present invention. DETAILED DESCRIPTION

[0025] In order to more clearly illustrate the purpose and technical advantages of the present invention, the present invention is further described below in conjunction with the embodiments. Obviously, the embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in this field without making creative work are all within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0027] The alumina particle size used in the following examples is 200-300 mesh.

[0028] The specification of powdered phenolic resin is 200 mesh and the molecular weight is 1800-2500.

[0029] Example 1 Slurry preparation

[0030] (1) Weigh liquid aluminum dihydrogen phosphate with a solute mass fraction of 50% as liquid A for later use.

[0031] (2) Preparation of liquid aluminum dihydrogen phosphate / alumina slurry - liquid B

[0032] Weigh 20 g of liquid aluminum dihydrogen phosphate with a solute mass fraction of 50% and 1.6 g of aluminum oxide powder, stir for 30 minutes to obtain liquid B-1 for use.

[0033] Weigh 20 g of liquid aluminum dihydrogen phosphate with a solute mass fraction of 50% and 3.2 g of aluminum oxide powder, stir for 30 minutes to obtain B-2 solution for use.

[0034] Weigh 20 g of liquid aluminum dihydrogen phosphate with a solute mass fraction of 50% and 4.8 g of aluminum oxide powder, stir for 30 minutes to obtain B-3 solution for use.

[0035] Weigh 20 g of liquid aluminum dihydrogen phosphate with a solute mass fraction of 50% and 6.4 g of aluminum oxide powder, stir for 30 minutes to obtain B-4 solution for use.

[0036] (3) Preparation of liquid aluminum dihydrogen phosphate / alumina / phenolic resin slurry-liquid C

[0037] To the B-2 solution, add 4.0 g of powdered phenolic resin and stir for 30 minutes to obtain C-1 solution for use.

[0038] On the basis of liquid B-2, add 2.0 g of powdered phenolic resin and stir for 30 minutes to obtain liquid C-2 for use.

[0039] To the B-2 solution, add 1.3 g of powdered phenolic resin and stir for 30 minutes to obtain C-3 solution for use.

[0040] On the basis of liquid B-2, add 1.0 g of powdered phenolic resin and stir for 30 minutes to obtain liquid C-4 for use.

[0041] The flow rate and specific gravity of each slurry were measured, and the results are shown in Table 1.

[0042] Table 1 Flow rate and specific gravity of each slurry

[0043]

[0044] Example 2: Body reinforcement

[0045] Liquid A, liquid B-1, liquid B-2, liquid B-3, liquid B-4, liquid C-1, liquid C-2, liquid C-3, and liquid C-4 were evenly applied to the bottom of the spare undried blank with a coating thickness of 0.3-0.5 mm, and samples A, B-1, B-2, B-3, B-4, C-1, C-2, C-3, and C-4 were prepared after drying. The performance of each sample was then tested.

[0046] Experimental results:

[0047] Table 2 and Figure 1The results of the strength test show that for different substrate materials, the coating can enhance the strength of the blank.

[0048] At the same time, it can be seen that liquid A has the most obvious reinforcing effect on Jersey stone powder, which has the lowest strength of the green body.

[0049] In liquid B, with the increase of alumina powder content, the green body strength first increases and then decreases. When liquid aluminum dihydrogen phosphate: alumina (molar ratio) = 1:1 (B-2), the green body has the highest flexural strength.

[0050] Based on the B-2 slurry formula, the introduction of phenolic resin can further improve the strength of the green body. Moreover, with the increase of phenolic resin content, the green body strength first increases and then decreases. When the liquid aluminum dihydrogen phosphate: phenolic resin (mass ratio) = 10:1 (C-2), the green body has the highest flexural strength.

[0051] Table 2 Strength of different coating formulas applied to the bottom of four types of blanks after drying (MPa)

[0052]

[0053] Figure 2 The figure shows the changes in the effects of liquid A, liquid B and liquid C on the bottom of the brick blanks on the production line, where the control example is a blank that is not coated with slurry.

[0054]

[0055] During the drying process, aluminum dihydrogen phosphate loses water and condenses into macromolecules (as shown in reaction formula (1)), which cross-link with each other to generate cohesive force and adhesion to the blank. The blank generates strength under the simultaneous action of these two forces.

[0056] Combination Figure 2 (a) and (b), after using liquid A in the comparative example, the bottom of the sample showed obvious dense micropores and microcracks. This is mainly because the first drying part forms strength before the slow drying part during the drying process of the green body, resulting in uneven stress distribution at the bottom of the green body. At the same time, due to the polycondensation reaction of aluminum dihydrogen phosphate, the 0.3-0.4mm surface layer at the bottom of the green body was damaged under the action of this uneven internal force, and finally a large number of microcracks were formed. Therefore, the coating thickness of the slurry is easy to be between 0.3-0.5mm, so that after drying, it basically covers the area at the bottom of the green body that is prone to microcracks.

[0057] from Figure 2 (c) It can be seen that the microcracks disappear after adding an appropriate amount of alumina powder to liquid A. This is mainly because alumina acts as an auxiliary agent, which can fill the gaps between aluminum dihydrogen phosphate and act as aggregate, thereby alleviating the effect of thermal stress and reducing the generation of microcracks.

[0058] from Figure 2 (d) It can be seen that the pores are further significantly reduced after adding an appropriate amount of phenolic resin to liquid B. The bonding process of phenolic resin includes two steps. The first is the penetration of phenolic resin into the bottom bumps and pores of the green body after heating; the second is the curing process of phenolic resin. In this process, cross-linking reaction occurs between its molecules to form a network structure, so that the resin molecules are embedded in the pores and bumps at the bottom of the green body, thereby forming a strong adhesion force to tightly bind the resin and ceramic particles together.

[0059] In summary, it can be seen that the slurry of the present invention can effectively strengthen the green body, and the raw materials are easily available and low in cost. When used, it can be directly coated on the bottom of the green body without involving the adjustment of the green body composition and without affecting other process parameters and performance indicators of the green body.

[0060] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0061] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A slurry for improving the strength of dry ceramic tiles, characterized in that: Including liquid aluminum dihydrogen phosphate and alumina powder.

2. The slurry according to claim 1, characterized in that In the slurry, the concentration of liquid aluminum dihydrogen phosphate is 50wt%, and the molar ratio is aluminum dihydrogen phosphate:alumina=1:0.5-2.

3. The slurry according to claim 2, characterized in that According to the molar ratio, aluminum dihydrogen phosphate: aluminum oxide = 1:

1.

4. The slurry according to claim 1, characterized in that The particle size of the aluminum oxide is in the range of 200-300 meshes.

5. The slurry according to any one of claims 1 to 4, characterized in that: The slurry also contains phenolic resin.

6. The slurry according to claim 5, characterized in that According to the mass ratio, liquid aluminum dihydrogen phosphate: phenolic resin = 10: 2 ~ 0.

5.

7. The method for preparing the slurry according to any one of claims 1 to 6, characterized in that: The slurry for improving the strength of the dry ceramic tile is obtained by mixing and dispersing the components uniformly.

8. The method for preparing the slurry according to claim 7, characterized in that: The flow rate of the slurry is in the range of 17-66 s, and the specific gravity is in the range of 1.40-1.61 g / ml.

9. A method for improving the strength of dry ceramic tiles, characterized in that: The method comprises the steps of: uniformly coating the slurry according to any one of claims 1 to 6 or the slurry prepared by the preparation method according to any one of claims 7 to 8 on the bottom of the green body to be dried.

10. The method according to claim 9, characterized in that The coating thickness of the slurry is 0.3-0.5 mm.